Evaluating the organic measure of a Mediterranean region rural development plan - Cembalo L.; D'Amico M.; D'Ercole E.; La Via G. (Food quality products in the advent of the 21st century: production, demand and public policy, 2005)
This paper attempts to evaluate the organic measure of the Rural Development Plan (RDP) in Campania, a Mediterranean region in Southern Italy. To do so, several criteria were considered: economic, environmental, and public expenses feasibility. As these criteria are conflicting, given that it is not simultaneously possible to achieve the optimal level of each, a multicriteria approach was adopted so as to reach the best compromise solution among the Pareto efficient ones. The results indicate that the RDP in Campania would be more efficient under two conditions: first, re-allocating financial subsidies more specifically on the basis of real environmental farm performance; and second, operating a horizontal and vertical integration of the organic sector.
83. EAAE Seminar on Food Quality Products in the Advent of the 21st Century: Production, Demand and Public Policy, 2003/09/04-07, Chania (Greece)